Current status and future challenges in continuous biochromatography. (December 2018) - Vogg, Sebastian; Müller-Späth, Thomas; Morbidelli, Massimo
Graphical abstract: Abstract : Continuous processing of biopharmaceuticals has seen increased interest in recent years due to more competition in the market as well as broader pipelines asking for more flexible and therefore intensified processes. For downstream processing, chromatography remains the separation process of choice due to its very high resolving power. While continuous counter-current processes have been implemented successfully in other sectors such as the petrochemical or small-molecule pharmaceutical industry, biopharmaceuticals bring new challenges to this field such as high mass transfer limitation due to their size. In this contribution, we present a concise review of continuous processes that have been developed or adapted to the needs of the biopharmaceutical sector and were successfully implemented at the lab scale. Furthermore, we highlight future challenges that need to be addressed both on the processing and the regulatory side. Resolving those will mature these processes to be employed at manufacturing scale. The discussed challenges include new operation modes as well as process scale-up and validation.